2004
DOI: 10.1111/j.0105-1873.2004.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact and photocontact allergy to ketoprofen. The Belgian experience

Abstract: Topical ketoprofen (KP) is widely used because of its anti-inflammatory effect. However, photocontact dermatitis is a side-effect. Between May 2001 and June 2002, the Belgian Contact & Environmental Dermatitis Group conducted a prospective, open patch and photopatch test study in 20 patients suspected of KP dermatitis. Severe skin symptoms requiring systemic corticotherapy occurred in 47%. 5 patients were hospitalized. 1 patient showed prolonged photosensitivity. All patients were tested with KP and the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 5 publications
(8 reference statements)
7
52
0
Order By: Relevance
“…The results showed that three patients out of 17 had a positive photo-patch test and two patients had a positive patch test to 5% neroli oil in alcohol. Out of 20 only one patient showed positive photo-patch test to 2% neroli oil in white petrolatum [47].…”
Section: Neroli Essential Oilmentioning
confidence: 96%
“…The results showed that three patients out of 17 had a positive photo-patch test and two patients had a positive patch test to 5% neroli oil in alcohol. Out of 20 only one patient showed positive photo-patch test to 2% neroli oil in white petrolatum [47].…”
Section: Neroli Essential Oilmentioning
confidence: 96%
“…Also fenofibrate, a systemic drug, shares the benzophenone ring and can cross react with ketoprofen and related molecules. 3,20 Furthermore, patients with PhACD from ketoprofen present with concomitant reactions to the perfume ingredient cinnamic alcohol, reactions that at present are difficult to explain by cross-reactivity. 21 Therefore, patch and photo-patch testing are highly recommended in patients with idiopathic and autoimmune photodermatoses, as well as in all other diseases aggravated by sunlight, in order to detect and avoid exposure to possible aggravating factors, and particularly to UV filters.…”
Section: This Number Of the Revista Da Sociedade Portuguesa Dementioning
confidence: 99%
“…Arylpropionic acid derivatives, mainly ketoprofen, are responsible for most reported cases of photoallergy (28,(98)(99)(100). Photocontact allergy to ketoprofen seems to induce a number of photo cross-reactions to compounds with structural similarity like benzophenone-3 and the lipid-lowering agent fenofibrate (78,101,102).…”
Section: Topical Nsaidsmentioning
confidence: 99%